Economics' wisdom deficit and how to reduce it - John F. Tomer (Economic Thought, 2020)
As is well understood, the values inherent in the dominant neoclassical economic paradigm are self-interest and optimisation. These are the values that guide individuals and policymakers in advanced capitalist economies in their economic decision making. As a consequence, the economics discipline, arguably, is insufficiently oriented to helping people and organisations make wise choices, choices about what is really and truly in people's best interests. In other words, there is strong reason to believe that economics has a wisdom deficit. This paper draws on great philosophers such as Aristotle to explain what wisdom is and why, although economics is concerned with the normative aspect of decision making, economics has too infrequently been used to help people or their societies make wise decisions. This paper is also concerned with how a society's economic decision-making processes can be improved in order that these processes incorporate a much greater dose of wisdom. One relevant question here is: can we learn with the help of philosophers, psychologists and organisation researchers how to make economic decisions that apply the practical wisdom that Aristotle advocated? This paper's overall purpose is first to point the way toward greater decision-making wisdom, and second to propose one method for improving the wisdom of important economic-related decision making. Hopefully, this paper will serve to put the issue of decision-making wisdom higher on the agenda of economists and, as a consequence, lead to wiser decisions in the economic sphere, thereby reducing the wisdom deficit.
Keywords: 330